Anti-Melanogenic Effect Of An Extraction Of Annona Muricata L. On B16F10 Cell - Shin, Yun-Mi; Kim, You-Jeong (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study was intended to investigate the melanin biosynthesis, and cell of Annona muricata leaves (A. muricata L) extract for evaluating potential as cosmetic material and industrial developing value. Methods/Statistical analysis: To measure prevention of melanin biosynthesis, B16F10 cell from A. muricata L extract was used to measure its melanin prevention function. Medium containing 5% blood serum and α-MSH 10 nM was added to promote melanin generation. By using microplate reader, the amount of melanin absorbed at 405nm was measured. For the amount of melanin generated, it is indicated in percentage after comparing it with comparison sample which only processed α-MSH 10 nM. Findings: To identify Anti-melanogenic effect of A. muricata L extract, this study clarifies that usability of B16F10 cell is only low at high concentration. melanogenesis was suppressed by concentration as a result of conducting an experiment of melanogenesis inhibitory activity by processing on B16F10 cell. This result deduces the possibility of searching whitening ingredients in natural products. A. muricata L Therefore, this study suggests the possibility of A. muricata L extract as a material with various functionalities as whitening, effect used as a functional cosmetic material. Improvements/Applications: Verification study for effects of A. muricata L extract needed to be conducted systematically in the future through biological and human studies to determine the clinical applicability.